Morphology like a tool to understand the social behavior in ant’s larvae - Ortiz, Gabriela [UNESP]; Mathias, Maria Izabel Camargo [UNESP]; Bueno, Odair Correa [UNESP] (My University, 2012)
All metamorphosing insects pass through four consecutive stages before reaching their adult form and these stages are known as the egg, the larva, the semipupa and the pupa. The larval stage comprising individuals who have completely different morphology of the other three, since the body is devoid of external appendages and with internally adipose tissue. From the larval stage begins the growth of individuals who shed their skins several times and depending on the insect considered the substages vary from 3 to 5. In bees in general there are five larval stages called L1 to L5, interspersed with each other for four periods of change ending in larval and pupal changes when successful-L5 larvae enter the pupal stage, where individuals have had adult characteristics. Since ants have about four larval stages (L1, L2, L3, L4), but this number can vary from 3 to 6 depending on the species. In the larvae of ants there are morphological peculiarities in certain species that set them apart from most reported in the literature so far. An interesting fact was observed in the Argentine ant Linepithema humile, an invasive species, since they present a dorsal protuberance in the sixth abdominal segment found exclusively in their larvae. Researchers have tried to explain the social function of this structure. One function described was the nutrition. However the morphological results obtained in this study suggested that the dorsal protuberance has no secretory function, since ducts or pore channels were not found, only small folds in the cuticle, which does not indicate a secretion release function. The secretion released is just for the cuticle compounds and does not synthesize other one which would be important in social behavior. Therefore the unique social function that can be attributed to the dorsal protuberance was mechanical or serving like a facilitator making it easier for the workers to transport the immatures through the different environments in the colony. Another relevant fact would be peculiar behavior observed in basal attine ants, which in addition to cultivating their fungus, still keeps the fungus growing externally on the surface of the cuticle’s larvae, behavior not seen in the genre Atta. Therefore was verified the alterations in the cuticle of the larvae from Myrmicocrypta, Mycetarotes and Trachymyrmex and this structure is formed by a simple cubic epithelium, whose cells possibly change its shape to prismatic, depending on their secretory activity. The presence of fungi hyphae was observed both on the external side of the basal attine larvae as well as emitting projections to the interior of the cuticle reaching the epithelium and the adipocyte cells. Some authors have suggested that the fungus could benefit the larvae protecting them against occasional pathogens by forming a physical or chemical barrier. Data obtained in this study demonstrated that the fungus deposited on the surface of immature from basal attine maintain a close relationship with them, once the fungus hyphae have the ability to disorganize the lamellar cuticle, penetrating the interior of the cells through the emission of prolongations.